A qualitative study of female caregiving spouses’ experiences of intimate relationships as cognition declines in Parkinson’s disease - Vatter, Sabina (Age Ageing, 2018)
BACKGROUND: the complex and progressive nature of Parkinson’s disease (PD) and cognitive impairment may necessitate a care provider, a role which is frequently undertaken by a spouse. Providing and receiving care related to dementia impacts on a couple’s partnership and may result in decreased intimacy and relationship satisfaction. OBJECTIVE: to explore the changes in long-term intimate relationships in Parkinson’s-related dementia, as perceived by spouses providing care to their partners. METHODS: participants were identified using purposive sampling. Twelve female spouses whose partners had PD and mild cognitive impairment (PD-MCI), PD dementia (PDD) or dementia with Lewy bodies (DLB) completed semi-structured face-to-face interviews. Transcribed data were analysed using inductive thematic analysis. The consolidated criteria for reporting qualitative research (COREQ) were applied. RESULTS: couples’ relationship satisfaction, intimacy and communication had already reduced in the mild cognitive impairment stage of PD, but the decline in these domains was markedly greater with the emergence of dementia. Increased spousal care responsibilities resulted in partners spending more time together, but feeling emotionally more distanced. Several participants’ roles transitioned from spouse to caregiver and they reported feelings of frustration, resentment, anger, sadness and a worry for the future. Cognitive impairment was significantly harder to accept, manage and cope with than the motor symptoms of PD. Spouses acknowledged their marital commitments and exhibited acceptance, adjustment, resilience and various coping strategies. CONCLUSION: this is the first study exploring relationship satisfaction in Parkinson’s-related dementia and has provided valuable insight into the changing patterns of intimate relationships.